Peran Pendampingan UMKM terhadap Penguatan Strategi Bisnis Lokal di Era Digital - Putra, Rally Immanuel Marno; Kurnia, Alvian Chandra (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in driving local economic growth. However, amidst the rapid digital transformation, many MSMEs are not yet ready to face these changes optimally. Mentoring is one of the crucial strategies in strengthening the competitiveness and adaptive capabilities of MSMEs to the dynamics of the digital market. This study aims to analyze the extent to which the role of mentoring contributes to strengthening local business strategies. The focus of the study includes aspects of training, digital transformation, business actor motivation, and obstacles in implementing mentoring. The findings show that systematic and sustainable mentoring can have a positive impact on the growth of MSMEs, especially in increasing digital literacy, product innovation, and more modern and efficient business management.